STRATEGI MANAJEMEN DIRI MENUJU PROFESIONALIME GURU - Ishartiwi Ishartiwi (Dinamika Pendidikan, 2009)
Teacher professionalism is an attitude that adheres to a techer as professional staff. The professional attitude can be indicated by the quality in performing his/her tasks. Professional  teacher base their task performance on self-awareness and responsibility for their profession. Teachers in performing their ran creativelly integrate the rules in their profession with the context faced in the field  The can also plan and perform self-professional development individually. The realization (~lthe teacher professionalism  achievement put more stress on the teacher ability for self-managing  to their profession rules In this  case teachers needs a self management  strategy involving comprehension  on the charakieristic. task and authoriiy of professional teacher and self-efforts to  achieve teacher professionalism as well as the ways to develop the attitude of self-proffesionalism as teacher. Key words: teacher sclf-managerment, profeesional teacher.